Performance and Return to Sport After Thumb Ulnar Collateral Ligament Surgery in National Football League Players. (July 2019) - Sochacki, Kyle R.; Jack, Robert A.; Nauert, Richard; Liberman, Shari R.; McCulloch, Patrick C.; Lintner, David M.; Harris, Joshua D.
Background: Acute ruptures of the ulnar collateral ligament (UCL) of the thumb are common injuries in sports. Surgical repair of complete tears has yielded excellent results in elite athletes.Methods: National Football League (NFL) players who underwent thumb UCL surgery and matched controls were identified. Demographic and performance data were collected. Performance scores were calculated using a standardized scoring system. Return to sport (RTS) in the NFL was defined as playing in at least 1 NFL game after thumb UCL surgery. Comparisons between case and control groups and preoperative and postoperative time points were made using paired-samples Student t tests.Results: Twenty-three players were identified (mean age: 28.8 ± 3.4 years and mean experience in the NFL: 5.9 ± 3.4 years). Twenty-two players (95.7%) were able to return to sport in the NFL at an average of 132.2 ± 126.1 days. The overall 1-year NFL career survival rate of players undergoing thumb UCL surgery was 87.0%. There was not a statistically significant decrease in games per season and career length for any position following surgery. No positions had a significant difference in postoperative performance when compared with preoperative performance, and there was no significant performance difference postoperatively when compared with matched controls.Conclusions: There is a high rate of RTS in the NFL following thumb UCL surgery. Players who underwent thumb UCL surgery played in a similar number of games per season and had similar career lengths in the NFL as controls. No position group had any significant postoperative performance score differences when compared with postindex matched controls.